2020
DOI: 10.1177/0883073820972507
|View full text |Cite
|
Sign up to set email alerts
|

Maternal Infection During Pregnancy and Risk of Cerebral Palsy in Children: A Systematic Review and Meta-analysis

Abstract: Background and aim: The association between maternal infection during pregnancy and the risk of cerebral palsy has been previously reported. However, their results were relatively inconsistent. This systematic review and meta-analysis were carried out to investigate the association between maternal infection during pregnancy and the risk of cerebral palsy in children. Methods: PubMed, Scopus, and Web of Sciences databases were searched from inception to October 28, 2019. Heterogeneity was assessed using the I2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 65 publications
1
6
0
Order By: Relevance
“…Moreover, almost all subgroup analyses according to type of studies, publication year, and diagnostic criteria also indicated a positive association. These findings are in line with previous meta-analyses indicating that maternal infection is associated with increased risk of psychosis, cerebral palsy, and autism spectrum disorders [ 12 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…Moreover, almost all subgroup analyses according to type of studies, publication year, and diagnostic criteria also indicated a positive association. These findings are in line with previous meta-analyses indicating that maternal infection is associated with increased risk of psychosis, cerebral palsy, and autism spectrum disorders [ 12 14 ].…”
Section: Discussionsupporting
confidence: 92%
“…There is a consensus in the literature that infections/inflammation via cytokinemediated injury to the immature brain are causally associated with CP (see Figure 2). Infection, inflammation and cytokines play a fundamental role in CP causation through their link with preterm labour (prematurity), placental pathology (chorioamnionitis, funisitis), congenital malformation, FGR, cerebral white matter injury (WMI) and perinatal asphyxia [29,[33][34][35][36][37]. Studies including recent meta-analyses have shown compelling evidence that maternal infections in pregnancy, intra-amniotic infection (chorioamnionitis), evidence of FIRS and neonatal infections are causally associated with CP [25,29,[35][36][37].…”
Section: Infection Inflammation and Cpmentioning
confidence: 99%
“…Infection, inflammation and cytokines play a fundamental role in CP causation through their link with preterm labour (prematurity), placental pathology (chorioamnionitis, funisitis), congenital malformation, FGR, cerebral white matter injury (WMI) and perinatal asphyxia [29,[33][34][35][36][37]. Studies including recent meta-analyses have shown compelling evidence that maternal infections in pregnancy, intra-amniotic infection (chorioamnionitis), evidence of FIRS and neonatal infections are causally associated with CP [25,29,[35][36][37]. Both transplacental TORCH infections (Toxoplasmosis, Others [syphilis, Epstein Barr virus, HIV, Zika virus], Rubella, Cytomegalovirus [CMV], Herpes virus), genitourinary infections (bacterial vaginosis, chlamydia, trichomonas, UTI) and neonatal infections (GBS-early onset sepsis, neonatal pneumonia, meningitis) have all been implicated in CP [37].…”
Section: Infection Inflammation and Cpmentioning
confidence: 99%
“…It is believed that clinical chorioamnionitis increases the risk of CP in term (relative risk = 4.7) and preterm infants (relative risk = 1.9), due to inflammatory response to intrauterine infection that causes periventricular leukomalacia [2]. It is essential to remember the coexistence of GUI and preterm births as the risk factors of cerebral palsy, since pregnant women with maternal infections tend to have preterm labour (before 32 week's gestational age) [3].…”
Section: Introductionmentioning
confidence: 99%